Designing Educational Video Games to Be Objects-to-Think-With. Issue 1 (1st January 2019) - Holbert, Nathan; Wilensky, Uri
Abstract : In this article we propose that educational game design should work to create games as objects-to-think-with—games that engage players in the exploration of and experimentation with personally interesting questions around domain-relevant representations. We argue that this design focuses on developing tools and interactions that the player can use for inquiry and productive thinking. As a step toward achieving this goal, we propose the constructible authentic representations design principle and illustrate this principle using a prototype game, Particles!, for exploring the particulate nature of matter. Observations of game play and interviews with 9 children ages 11–14 suggest that core game representations and mechanics provided players with a space for engaging in useful scientific practices and knowledge resources for reasoning about the important role molecular structure plays in material properties beyond the game. We explore how this design proposal extends and complements existing constructivist game design frameworks. Furthermore, we suggest that the framework of games as objects-to-think-with should push the educational game design community to consider the complexity and nuance of cognition and to embrace and champion the learner in game design.